2017
DOI: 10.1186/s41043-017-0107-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of antenatal care and place of delivery with newborn care practices: evidence from a cross-sectional survey in rural Uttar Pradesh, India

Abstract: BackgroundAppropriate immediate newborn care is vital for neonatal survival. Antenatal period is a crucial time to impart knowledge and awareness to mothers regarding newborn care, either during facility visits or during home visits by community health workers (CHWs) especially in the rural context. In this paper, we report newborn care practices in rural Uttar Pradesh (UP) and have explored association between newborn care practices with antenatal care, contact with community health workers during pregnancy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 14 publications
6
21
3
Order By: Relevance
“…Studies showed that, even in the case of villages where SHG only programs were present, membership was not associated with higher antenatal care, institutional delivery or post-natal care (58)(59)(60). While increasing parity is also likely to be correlated with increasing age, the lower level of knowledge of danger signs found in our study with increasing parity could also be in uenced by increasing age.…”
Section: Individual Health and Health System Variablescontrasting
confidence: 63%
See 1 more Smart Citation
“…Studies showed that, even in the case of villages where SHG only programs were present, membership was not associated with higher antenatal care, institutional delivery or post-natal care (58)(59)(60). While increasing parity is also likely to be correlated with increasing age, the lower level of knowledge of danger signs found in our study with increasing parity could also be in uenced by increasing age.…”
Section: Individual Health and Health System Variablescontrasting
confidence: 63%
“…Studies elsewhere have shown that membership in the SHG only program has a limited association with improving routine maternal and newborn health (MNH) practices. For example, three recent studies in rural UP showed that membership in SHG only programs did not improve the practice of three antenatal care check-ups, institutional delivery or post-natal care, but the selectively improved practice of newborn cord care (58)(59)(60). Similar inferences were also drawn from a larger 2019 study from UP that concluded that there were signi cant improvements (5-11 percentage points) in desired Maternal and Neonatal…”
Section: Discussionmentioning
confidence: 79%
“…This can be explained by the fact that mothers who received training on essential newborn care during ANC, delivery and PNC periods could better understand the importance of the practice of essential newborn care [30]. There may be other possible reasons community health workers (HEWs) could discuss and educate about ENBC during monthly meeting [31]. Thus, to support the utilization of health facilities for prevent and treat neonatal mortality and morbidity, prompt postnatal care (PNC) for the mother and the child is important.…”
Section: Discussionmentioning
confidence: 99%
“…Similar finding was reflected in a study by Niveditha Det al in India. 14 Regarding the reason for selecting UHC for the place of delivery, 51.3% respondents preferred for avoiding pregnancy related complications (Fig -1)…”
Section: Discussionmentioning
confidence: 99%